Factors Associated with Recurrent Stroke Among Inpatients at Adam Malik General Hospital: A Case-Control Study - Savina Talitha Jasmine; Nofi Susanti; Hasrat Efendi Samosir; Yulia Khairina Ashar; Lambok Rumiris Situmorang (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Recurrent stroke is a major public health concern because it is associated with increased mortality, disability, hospitalization, and healthcare burden. This study aimed to identify factors associated with recurrent stroke among inpatients at H. Adam Malik General Hospital from 2023 to 2025. Method: This retrospective case-control study included 222 stroke inpatients, consisting of 111 patients with recurrent stroke and 111 patients with first-ever stroke. Cases were selected using total sampling, while controls were selected using quota sampling with a 1:1 ratio. Data were obtained from medical records. The independent variables were age, sex, hypertension, type 2 diabetes mellitus, coronary heart disease, and obesity. Data were analyzed using Chi-square tests and multiple logistic regression. Result: Bivariate analysis showed that age ≥55 years (OR=2.057; 95% CI: 1.107–3.821; p=0.021), male sex (OR=1.927; 95% CI: 1.130–3.286; p=0.016), type 2 diabetes mellitus (OR=2.088; 95% CI: 1.219–3.576; p=0.007), and coronary heart disease (OR=3.200; 95% CI: 1.634–6.267; p=0.001) were significantly associated with recurrent stroke. In the multivariate model, age ≥55 years (aOR=2.381; 95% CI: 1.208–4.696; p=0.012), male sex (aOR=1.852; 95% CI: 1.092–3.141; p=0.024), type 2 diabetes mellitus (aOR=2.124; 95% CI: 1.203–3.751; p=0.010), and coronary heart disease (aOR=3.200; 95% CI: 1.634–6.267; p=0.004) remained significantly associated with recurrent stroke. Coronary heart disease showed the strongest association. Conclusion: Recurrent stroke was associated with age ≥55 years, male sex, type 2 diabetes mellitus, and coronary heart disease. Coronary heart disease was the dominant associated factor after adjustment for other variables. Comprehensive secondary prevention targeting cardiovascular and metabolic comorbidities is essential to reduce recurrent stroke risk.